Exploring the relationship between polygenic risk for cannabis use, peer cannabis use and the longitudinal course of cannabis involvement. (1st January 2019) - Johnson, Emma C.; Tillman, Rebecca; Aliev, Fazil; Meyers, Jacquelyn L.; Salvatore, Jessica E.; Anokhin, Andrey P.; Dick, Danielle M.; Edenberg, Howard J.; Kramer, John R.; Kuperman, Samuel; McCutcheon, Vivia V.; Nurnberger, John I.; et al.
Abstract: Background and aims: Few studies have explored how polygenic propensity to cannabis use unfolds across development, and no studies have yet examined this question in the context of environmental contributions such as peer cannabis use. Outlining the factors that contribute to progression from cannabis initiation to problem use over time may ultimately provide insights into mechanisms for targeted interventions. We sought to examine the relationships between polygenic liability for cannabis use, cannabis use trajectories from ages 12–30 years and perceived peer cannabis use at ages 12–17 years. Design: Mixed‐effect logistic and linear regressions were used to examine associations between polygenic risk scores, cannabis use trajectory membership and perceived peer cannabis use. Setting: United States. Participants: From the Collaborative Study on the Genetics of Alcoholism (COGA) study, a cohort of 1167 individuals aged 12–26 years at their baseline (i.e. first) interview. Measurements: Key measurements included life‐time cannabis use (yes/no), frequency of past 12‐month cannabis use, maximum life‐time frequency of cannabis use, cannabis use disorder (using DSM‐5 criteria) and perceived peer cannabis use. Polygenic risk scores (PRS) were created using summary statistics from a large ( n  = 162 082) genome‐wide association study (GWAS) of cannabis use. Findings: Three trajectories reflecting no/low ( n  = 844), moderate ( n  = 137) and high ( n  = 186) use were identified. PRS were significantly associated with trajectory membership [ P  = 0.002–0.006, maximum conditional R 2  = 1.4%, odds ratios (ORs) = 1.40–1.49]. Individuals who reported that most/all of their best friends used cannabis had significantly higher PRS than those who reported that none of their friends were users [OR = 1.35, 95% confidence interval (CI) = 1.04, 1.75, P  = 0.023]. Perceived peer use itself explained up to 11.3% of the variance in trajectory class membership (OR = 1.50–4.65). When peer cannabis use and the cannabis use PRS were entered into the model simultaneously, both the PRS and peer use continued to be significantly associated with class membership ( P  < 0.01). Conclusions: Genetic propensity to cannabis use derived from heterogeneous samples appears to correlate with longitudinal increases in cannabis use frequency in young adults.